A Dataset of Lower Band Whistler Mode Chorus and Exohiss with Instrumental Noise Thresholds - Ondřej Santolík; Ivana Kolmašová; Ulrich Taubenschuss; Miroslav Hanzelka; David P. Hartley (Scientific Data)
Abstract We describe a large database of natural electromagnetic emissions of lower band whistler mode chorus and exohiss within the Earth’s magnetosphere. It is based on more than 124 million selected survey measurements of magnetic fluctuations, recorded between 2001 and 2020 by the two NASA Van Allen Probes and four ESA Cluster spacecraft. The database provides a comprehensive view of amplitudes of these important electromagnetic emissions in the audible frequency range. We carefully condition the data to minimize the influence of instrumental artefacts. We also remove all data points which may be contaminated by instrumental noise using a newly developed method to define detection thresholds as a function of frequency, time, and instrument settings. The database can serve as a valuable resource for a broad range of scientists studying space weather, magnetospheric physics, and radiation belt dynamics.